Closing the Objectivity Loophole in Bell Tests on a Public Quantum Computer - Adam Bednorz; Josep Batle; Tomasz Białecki; Jarosław K. Korbicz (Advanced Quantum Technologies, 2026)
ABSTRACT We have constructed and run a Bell test of local realism focusing on the objectivity criterion. Objectivity means that the outcomes are macroscopically confirmed by a few observers at each party. The IBM Quantum and IonQ devices turn out to be sufficiently accurate to pass such an extended Bell‐type test, although at the price of communication loopholes and residual but statistically significant signaling. The test also serves as a benchmark of entanglement spread across larger sets of qubits.